Effect of Parameters on Carbon Nanotubes Grown by Floating Catalyst Chemical Vapor Deposition - lim, shiyi (2012)
There is a critical need to understand the effect of the growth parameters on the characteristics of carbon nanotubes (CNTs) in order to optimize the process for the production of CNTs with specific characteristics that will exhibit enhanced functionality for the application. Floating Catalytic Chemical Vapor Deposition (FCCVD) is a promising method to produce high yield bulk CNTs. Effects of parameters namely flow rate of ethylene and argon, reaction temperature and weight of ferrocene on CNTs grown by FCCVD were investigated. The growth of CNTs began with the vaporization of an amount of ferrocene at 150 C under argon ambient followed by exposure to ethylene at different temperatures. Properties of CNTs such as crystallinity and diameter were determined using Scanning Electron Microscopy and Transmission Electron Microscopy and Raman Spectroscopy. Temperature of 800 C and 850 C are found to be suitable for CNTs growth with the temperature of 850 C producing bigger diameter CNTs. Low flow rate of ethylene (20 sccm) produced CNTs with higher degree of crystallinity.